Improved nutritional quality in fruit tree species through traditional and biotechnological approaches. (November 2021) - Sabbadini, Silvia; Capocasa, Franco; Battino, Maurizio; Mazzoni, Luca; Mezzetti, Bruno
Abstract: Background: The increasing evidences on the relation between diet and human health are driving the consumers toward the choice of foods with high amount of nutrients, considered the molecules responsible for the regulation of several metabolic and biochemical processes, and for the prevention of many chronic diseases. Among food products, fruits represent a natural source of many different nutrients and possess much importance in a balanced diet. The increase of the micro/macronutrient levels and the decrease of antinutrients amount are considered main objectives for the improvement of fruit trees nutritional value. Scope and approach: This review summarizes many of the attempts made to increase the nutritional quality of fruit tree species during the last decades through the application of traditional and molecular breeding technologies, and the most recent New breeding techniques (NBTs). Key findings and conclusions: New genotypes with improved nutritional quality have been obtained for different fruit tree species, either by increasing the content of well-known beneficial molecules, such as phenolic compounds, vitamins, and carotenoids, or by decreasing the levels of specific antinutrients. The development of molecular techniques and biotechnological tools allowed the identification and validation of candidate genes involved in the regulation of specific classes of nutritional compounds in fruit trees, and useful to obtain nutritionally improved products. NBTs represent alternative tools to classical breeding techniques, to regulate one or more fruit trees key nutrients in a more quick and precise manner. However, genetic engineering approaches still present public and regulatory concerns that strongly limit their exploitation. Highlights: Fruit consumption provides essential macro and micronutrients for human health Conventional breeding is widely used, but presents several limitations Molecular techniques can be applied to assist and optimize conventional breeding New biotechnological tools allow the engineered introduction of quality traits Genetic engineering approaches still present public and regulatory concerns